(untitled) (World of finance, 2024)
Introduction. Modern challenges in the field of administration of tax payments have become especially acute for Ukraine in the conditions of the outflow of human capital and the loss of economic potential. Under such conditions, the role of tax transparency is decisive, because during the implementation of the administration process, it is a necessary prerequisite for the implementation of the basic principles of taxation - fairness and certainty. The purpose of this article is to determine the place of tax transparency in the tax payment administration system. Results. The evolutionary aspect of the formation of the definition was studied and the author’s definition of the term “tax transparency” was given. The place of tax transparency in the system of administration of tax payments in the context of the implementation of the administration of tax payments is determined, taking into account potentially possible scenarios of the development of events and actions on the part of taxpayers and tax administrations. The current state of implementation of tax transparency in Ukraine in comparison with other countries is studied. The vector of future necessary transformations of relations between taxpayers and the tax service in Ukraine for the implementation of the strategy of tax transparency is outlined. Conclusions. The dynamics of the development of international taxation, especially in the modern realities of the development of public finances of Ukraine, requires a rethinking of approaches to the process of implementing tax administration. The study of directions for increasing the efficiency of the administration process is the subject of further scientific research through the implementation of tax transparency, in particular, by building a close relationship and trust between taxpayers and the tax service.